Manajemen Kurikulum Perspektif Oliva : Telaah Epitemologis - Istianatul Hasanah (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Curriculum management is a system of curriculum management that is cooperative, comprehensive, and systematic in order to realize the achievement of curriculum objectives. A good curriculum is a curriculum that follows the development of science and technology based on society. The management of a curriculum determines success and failure in education. Therefore, Management curriculum is Importent thing in a scool education by principle education process which can work running wellby reaching a goal, such is garduate competent standardthat must be domeneted by student and motivated the teacher to alwasy implement the education.